USE OF REMOTE EDUCATIONAL TECHNOLOGIES IN TRAINING MATHEMATICS - Surkhayev, M.A.; Gerbekov, H.A.; Kubekova, B.S. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
The prospect of using distance learning on classes in mathematics and also requirements to ICT competence of mathematics teacher in the conditions information and education environments of educational organization are discussed in article. Requirements to ICT competence of a teacher are formulated in the professional standard for teacher and caused by the fact that the huge potential of information and education environment of educational organization remains unrealized mostly because there isn’t enough teachers capable and ready to use possibilities of new educational environment to increase efficiency of educational process. If today the all-user ICT- competence including knowledge of bases hardware and the software of the computer as the instrument of work in modern information space and necessary for the teacher to work with text editors, spreadsheets, e-mail and browsers, the multimedia equipment already is at the sufficient level at most of teachers, then all-pedagogical andsubject and pedagogical ICT-competence leaves is much to be desired, All-pedagogical and subject pedagogical ICT- competence are necessary for a teacher in particular for introduction electronic training and distance educational technologies. Implementation of distance learning allows to increase a share of independent work of pupils and to make active, develop ability of search, the analysis and synthesis of information.